Spatio-Temporal Variations in Paddy Cultivation: A Case Study of Paschim Medinipur District, West Bengal - Samanta, Rajeeb; Bajpai, Ranjana (National Geographical Journal of India, 2022)
Agricultural growth leads to broad-based economic growth and development as linkages between farm and non-farm economies generate income and growth. Agricultural growth, in true sense denotes a change in crop area and production over different time periods. It plays a key role in alleviation and eradication of rural poverty and hunger. Paschim Medinipur district is predominantly an agricultural district of West Bengal where more than 80 percent of the total population resides in the villages, with surplus production of paddy, vegetables and potato. The cultivators constitute 22.80 percent of the total working population of 25.91 lakhs in the district; small and marginal farmers comprise 31.14 percent of the total cultivators and contribute 28.39 percent to Net District Domestic Product. Present study is focused upon the changing growth pattern and instability in area and yield of major paddy varieties (aus, aman, boro) in Paschim Medinipur district from 1992-93 to 2012-13, at district and blocks. Growth and instability in paddy have been measured by growth rate (%) and Cuddy Della Valle Index (CDVI) respectively. The study reveals that positive growth rate in area was found in case of boro, whereas growth in area under aus and aman was found to be negative. Seasonal and annual variability in monsoon contributes to the annual variability of growth in area and yield of aus and aman. Overall, there was stability in area and yield for all the three crops in the district, but there were widespread intra-block disparities in crop area and production in the district in terms of growth and instability.